The effect of work stress and work discipline on turnover intention of pt ultrajaya milk industry & trading company employees - Fathari, Farrel Ahmad; Oktafien, Shinta (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
One of the challenges in the business world, especially in the manufacturing industry, is turnover intention. The impact is in the form of increased employees who think about leaving the company, feeling the pressure of the workload, lowering the company's image, as well as a work environment that is not good for workers. This study aims to examine and analyse the effect of work stress and work discipline on the employee turnover intention of PT Ultrajaya Milk Industry & Trading Company. The sampling method used simple random sampling. A questionnaire was used to collect data directly. The analytical method uses the process of testing classical assumptions, which include the processes of testing normality, testing heteroscedasticity, testing multicollinearity, and analysing multiple linear regression using the IBM SPSS 23 program. The study's findings show that the partial variable of work stress has a positive and large impact on turnover intention, whereas the partial variable of working discipline has no positive and insignificant impact. Meanwhile, multiple linear regression shows that it, along with work stress and work discipline, has a significant impact on turnover intention.